Local homelands and national projects: territorial representations in the Bulgarian press from the 1840s to the Russo-Turkish War (1877–1878) - Lilova, Dessislava (Historein, 2016)
This article analyses the representations of the local sense of place in the Bulgarian press from the 1840s to the end of the period of Ottoman rule (1878). Three major topics are outlined: the mediatisation of the local through the domestic news flow; the statistical quantification of the local sense of place by means of geographical descriptions; the local mobilisations during the Russo–Turkish War (1877–1878) which did not meet the expectations of national ideologists. The aim is not only to investigate the mechanisms of integrating the “little homelands” into the national project but to take into account the slow and difficult process of internalising the imagined Bulgarian homeland that took place in the microlaboratories of local communities.